(untitled) (Research, Society and Development, 2022)
Background: Several decades ago there have been transverse and longitudinal facial asymmetries at the time of bone growth, it is due to this that authors such as Haas began to use the rapid disjunction of the jaws, where it was visualized that these devices guide growth, improve breathing and correct dentofacial asymmetries. The most used devices are the Haas and Hyrax, which have the same objective and are only differentiated by the type of clothing and hygiene. Objective: The purpose of this literature review is to determine the positive effects produced by the Hyrax and Haas RME on transverse dentofacil defects, especially class III, and respiration in growing children. Materials and Methods: The type of research carried out was descriptive, establishing as a sample the articles published between 2006 and 2021, which were collected and found in the PubMed and Science Direct databases, using the search terms in English effects AND maxilla AND orthodontics AND palatal expansion technique AND children and their counterparts in Spanish, which were searched through the web page of descriptors in health sciences (DeSC) and which were determined by the PICO of the present investigation. Clinical cases, systematic reviews and meta-analyses carried out from 2006 to 2021 that met the research criteria were considered as inclusion criteria, and any disclosure of books, theses and monographs published from 2006 to 2021 was eliminated as exclusion criteria. The total number of articles found in the different search pages was 21, of which 11 were extracted from PubMed (National Library of Medicine) and 10 articles from Science Direct, which helped us develop this bibliographic review. Conclusion: The rapid expansion of the transverse maxilla results in the opening of the suture from 12 to 14 mm, thus being the most important positive effect produced by the RME Hyrax and Haas that resolves transverse dentofacial defects and helps the expansion of the nasal cavity. improving respiratory quality in growing children.